2013
DOI: 10.5014/ajot.2013.008417
|View full text |Cite
|
Sign up to set email alerts
|

Five Years Later: Achieving Professional Effectiveness to Move Neurorehabilitation Forward

Abstract: The AOTA Centennial Vision outlined in 2007 challenged the occupational therapy profession to become a "powerful, widely recognized, science-driven, and evidence-based" profession that could adapt to changing societal and cultural needs and flourish well into the future. That challenge can be met by simply being effective at what we do; this will increase our value and validate our worth. Neurorehabilitation in occupational therapy can also thrive if we verify that the interventions we use and the strategies w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…The scholarly practitioner, also referred to as "scholar," represents someone who demonstrates a lifelong commitment to excellence in practice through continuous learning, engaging in evidence-informed decision-making, and contributing to scholarship and knowledge translation [2]. Research regarding professionals who adopt a scholarly approach to practice has shown benefits for the individual clinician (e.g., validates the provider's work and their profession) [3], the organization (e.g., reduction in staff turnover, increased productivity and efficiency) [4,5], and most importantly, patients in the health care system (e.g., lower rate of mortality and adverse events) [6].…”
Section: Introductionmentioning
confidence: 99%
“…The scholarly practitioner, also referred to as "scholar," represents someone who demonstrates a lifelong commitment to excellence in practice through continuous learning, engaging in evidence-informed decision-making, and contributing to scholarship and knowledge translation [2]. Research regarding professionals who adopt a scholarly approach to practice has shown benefits for the individual clinician (e.g., validates the provider's work and their profession) [3], the organization (e.g., reduction in staff turnover, increased productivity and efficiency) [4,5], and most importantly, patients in the health care system (e.g., lower rate of mortality and adverse events) [6].…”
Section: Introductionmentioning
confidence: 99%
“…Recent reviews of rehabilitation research have called on occupational therapists to increase the volume and quality of research (Rao, 2012); however, in addition to increasing the number and quality of studies conducted, a critical component will be to produce research that focuses on participation, activity, and occupations, the seminal characteristics of our practice, as past rehabilitation reviews have emphasized (Doucet, 2013;Gillen, 2010;Rao, 2012;Wolf, 2011).…”
mentioning
confidence: 99%